A Copper(I)‐Catalyzed Three‐Component Domino Process: Assembly of Complex 1, 2, 3‐Triazolyl‐5‐Phosphonates from Azides, Alkynes, and H‐Phosphates. Issue 43 (23rd September 2013) - Li, Lingjun; Hao, Guoliang; Zhu, Anlian; Fan, Xincui; Zhang, Guisheng; Zhang, Lihe
<x xml:space="preserve">Abstract</x> Three is better than one! A new copper‐catalyzed tricomponent reaction of a terminal alkyne, organic azide, and H‐phosphate (CuAA[P]C) leads to a structurally diverse polysubstituted 1, 2, 3‐triazolyl‐5‐phosphonate, which provides an efficient tool for the direct introduction of phosphonic acid groups by a "click reaction" (see scheme).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>